2021
DOI: 10.3389/fpsyg.2021.660777
|View full text |Cite
|
Sign up to set email alerts
|

Fear of the Unknown: Does Fear of Terrorism Differ From Fear of Contracting COVID-19?

Abstract: The aim of the study was to explore whether living under constant security threat would result in better coping and higher resilience when exposed to an unknown threat such as the COVID-19 pandemic. Thus, fear of COVID-19 and fear of terrorism as well as the associations with coping strategies and resilience were examined among Israelis living in conflict zones as well as Israelis living in the center, where exposure to security incidents is rare. Six hundred and fifteen Israeli adults (260 men and 356 women) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…During the COVID-19 outbreak, Zhu et al ( 81 ) conducted a survey on mental health status of Chinese employees and found that 30.8% of employees experienced significant stress responses, 51.3% experienced mild to moderate depressive responses, and 43.3% experienced mild to moderate anxiety responses. Similarly, most people experienced psychological problems (i.e., anxiety, stress, depression) ( 79 , 83 ) and have a tendency to suicide ( 84 ) under the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 outbreak, Zhu et al ( 81 ) conducted a survey on mental health status of Chinese employees and found that 30.8% of employees experienced significant stress responses, 51.3% experienced mild to moderate depressive responses, and 43.3% experienced mild to moderate anxiety responses. Similarly, most people experienced psychological problems (i.e., anxiety, stress, depression) ( 79 , 83 ) and have a tendency to suicide ( 84 ) under the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the estimation of emotional well-being is related to the specific timing of the post-COVID-19 data collection which has been delayed compared to the lockdown release. Another possible explanation can refer to the habituation process (Shechory Bitton & Laufer, 2021). The continuous threat associated with the prolonged exposure to the COVID-19 pandemic, although just for two months, might have impacted whether a process of habituation occurred over time, moderating the impact on negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Terrorist attacks and criminal offences differ in regard to motivations and goals (Brück & Müller, 2010 ; Hasisi et al, 2020 ) as well as victim and offender characteristic (Lowry & Lating, 2002 ). Yet, both terrorist attacks and criminal offences are forms of violence (Nellis, 2009 ; Warr, 1984 ) that can cause injuries and death, disturb the social fabric of life (Ganor, 2005 ; Zemishlany, 2012 ), impair personal wellbeing (Cohen-Louck, 2019 ; Hoffman et al, 2016 ; Solomon et al, 1988 ), and create fears (Ganor, 2005 ; Zemishlany, 2012 ) not just in the victims but also in the general public (Alfaro-Beracoechea et al, 2018 ; Box et al, 1988 ; Brück & Müller, 2010 ; Cohen-Louck, 2019 ; Hale, 1996 ; Hoffman et al, 2016 ; Park et al, 2011 ; Rader, 2017 ; Shechory Bitton & Laufer, 2021 ).…”
Section: Fear Of Crime and Fear Of Terrorismmentioning
confidence: 99%
“…One of the factors related to fear of terrorism is coping style (Cohen-Louck & Ben-David, 2017 ; Shechory Bitton & Laufer, 2021 ), which refers to thoughts and acts that people use to manage stressful events (Folkman et al, 1987 ). Lazarus and Folkman ( 1984 ) identified two coping styles: problem-focused and emotion-focused (Lazarus & Folkman, 1984 ).…”
Section: Fear Of Terrorism and Coping Stylesmentioning
confidence: 99%
See 1 more Smart Citation